Electrical and thermal analyses of catheter-based irreversible electroporation of digestive tract. (1st January 2019) - Ren, Fenggang; Li, Qingshan; Gao, Xuyao; Zhu, Kun; Zhang, Jing; Chen, Xue; Yan, Xiaopeng; Chu, Dake; Hu, Liangshuo; Gao, Zhongquan; Wu, Zheng; Wu, Rongqian; et al.
Abstract: Introduction: Irreversible electroporation (IRE) combined with a catheter-based electrode during endoscopy is a potential alternative treatment method for digestive tract tumors. The aim of this study was to investigate the electrical injury (EI) and thermal injury (TI) to the digestive tract via numerical analyses and to evaluate the role and impact of electrode configurations and pulse settings on the efficacy and outcomes of IRE. Materials and methods: A finite element method was used to solve the numerical model. A digestive tract model having 4-mm-thick walls and two catheter-based electrode configuration models were constructed. The distributions of electric fields, temperature, electrical conductivity, tissue injury and limitation on the pulse number required for IRE were calculated and compared. Results: Electrode length is an important geometric parameter for electrodes in the monopolar model (MPM), while electrode spacing affects the outcomes in the bipolar model (BPM). Increasing the pulse voltage reduces the pulse number required for tissue ablation, while increasing the risk of TI. In total, there were 6 NT-IRE protocols, 12 thermal-IRE protocols and 30 TI protocols. All of the NT-IRE protocols were set in BPMs with a voltage of 0.50 kV. With increasing electrode spacing, the minimum pulse number decreased. However, thermal effects were inevitable in the MPM. Conclusions: The electrode configuration and pulse settings are adjusted to achieve NT-IRE synergistically. The BPM is more reliable for achieving NT-IRE in 4-mm-thick digestive wall. Future in vitro and in vivo studies are needed to support and validate this conclusion.